Morphology of aluminium with nickel addition on sand casting process - Puspitasari, P. (International OCSCO World Press, 2018)
Purpose: his research aimed to examine the morphology, elemental changes, and phase in the aluminium cast alloys with variations in nickel addition of 1, 2 and 3. Design/methodology/approach: Aluminium 98 was melted in sand casting process. The sand casting process was operated at 7000C and atmospheric pressure. The addition of nickel contain of 92.19 of its element. Specimens consist of 4 pieces Al-Ni with the size of 1 Ã 1 Ã 0.5 cm for morphological testing, while for phase identification testing consist of 4 pieces Al-Ni with the size of 1 Ã 1 Ã 2 cm. The morphological testing was performed using FEI Inspect S50 Scanning Electron Microscope (SEM) and the phase characterisation was conducted using Nikon ME5 Optical Microscope. Findings: The results showed that the addition of 1 nickel in the aluminium cast product could affect the morphology in granular shape with as similar size, at 2 nickel addition also has granular shape, while at 3 of nickel addition, the morphology of Al-Ni was in elongated shape. Phase identification of Al-Ni cast alloy shows that there were Al matrix with nickel that spread in grain boundary of Al. By increasing the percentage of nickel, it shows that the nickel dominated the grain boundary of Al. These results shows that Al-Ni alloy can be produced at simple route on sand casting process. Research limitations/implications: Sand casting process with 80 silica sand, 10 bentonite, 5 water. Raw material of aluminium contains of 92-99 of purity. Nickel as addition element contain of 90-92 purity. Practical implications: The addition of nickel should be prepared wisely in term of the calculation of alloying treatment because it will effect the mechanical properties of Al alloy itself. This research can be improved by varying the temperature of casting process, variation of nickel percentage, and observation of mechanical properties of Al-Ni alloy. Originality/value: Simple route of making Al-Ni alloy using sand casting method in laboratory and also the observation of nickel addition in aluminium matrix as the result of casting product. Â© International OCSCO World Press. All rights reserved. 2018.